Numerical study of transverse flow through banks of tubes using curvilinear coordinates - Rojo, Jesús; Rincón, José; Reyes, Miguel (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The scope of this work is to develop a numerical method to calculate the laminar flow through lube arrangements such as those in heat exchangers. To achieve this purpose, a non-staggered grid arrangement in curvilinear coordinates s is used. The differential equations that describe the flow and heat transfer are transformed and expressed in conservative form. The discretisation of the governing equation is carried out using the integration by means of the finite volumes method. The solution procedure uses the Cartesian components of velocity as dependent variables and the SIMPLER method to attain the pressure-velocity field coupling. Convective terms are approximated by using a high order treatment. The numerical model was applied lo several cases in laminar regime and the predictions obtained were compared with experimental and numerical works of several bibliographic sources, showing that the method is stable an accurate for the range of Reynolds numbers studied.